2016
DOI: 10.1108/ijlm-01-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cross-functional integration processes

Abstract: Purpose – The purpose of this paper is to characterize the cross-functional integration processes between marketing and logistics, while considering five basic elements: boundary spanning activities, integration factors, level of integration, formality/informality and impacts of integration. Design/methodology/approach – After an extensive literature review, five case studies were performed and in-depth interviews conducted. Both within-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(114 citation statements)
references
References 51 publications
4
96
0
14
Order By: Relevance
“…On the other hand, the same studies show that collaboration has a strong positive relationship with the performance of departments and the organization as a whole. Pimenta et al (2015) identified five types of factors present in the integration processes: 7…”
Section: Cross-functional Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the same studies show that collaboration has a strong positive relationship with the performance of departments and the organization as a whole. Pimenta et al (2015) identified five types of factors present in the integration processes: 7…”
Section: Cross-functional Integrationmentioning
confidence: 99%
“…To better understand cross-functional integration, Pimenta et al (2015) have derived five types of factors present in the cross-functional integration process. These are: points of contact, integration factors, formality/informality, integration level, and integration impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of cross-functional integration consists of five elements (Pimenta et al, 2016). These elements are boundary spanning activities, Integration factors, level of integration, formality/informality, and impacts of integration.…”
Section: Introductionmentioning
confidence: 99%
“…Management must evaluate their current operational model and strive to find and integrate key SCM business processes along all principal participants to achieve the potential benefits from an integrated supply chain. This can include; cost reduction, generation of added value, reduction of cycle time, and development of competitive advantage (Halldorsson et al, 2007;Oliveira et al, 2016;Pimenta et al, 2016). This will help businesses focus on developing an entire PSSC to operate as a unique entity guided to fulfil the market demand for maintenance services.…”
Section: Managerial Implicationsmentioning
confidence: 99%